Association of Exercise With Vascular Function in Patients With CKD: A Meta-Analysis of Randomized Controlled Trials - Wang, Huan; Xie, Dengpiao; Wu, Lisheng; Zhao, Liangbin (Frontiers in Medicine, 2022)
Background and aims: Vascular function is associated with an increased risk of cardiovascular events in patients with chronic kidney disease (CKD). Whether exercise improves vascular function in such patients remains controversial. This study aimed to conduct a meta-analysis on the effect of exercise training on the vascular function of patients with CKD. Methods: Embase, the Cochrane Central Register of Controlled Trials, and Medline were searched from inception until November 15, 2021. The terms exercise, chronic kidney disease, dialysis, kidney transplant, and randomized controlled trial were searched alone or in combination. Randomized clinical trials (RCTs) were included when studies compared exercise with active control, usual care, or no intervention, and the studies reported vascular function on patients with CKD. Results: This meta-analysis included 18 RCTs with 817 patients. Exercise training was significantly associated with decreased pulse wave velocity [weighted mean difference (WMD), -0.56; 95% confidence interval (CI), -1.02 to -0.09, P = 0.02] and augmentation index (WMD, -3.26; 95% CI, -5.46 to -1.05, P = 0.004). It was also significantly associated with improved peak VO2 (WMD, 2.64; 95% CI, 1.94 to 3.35, P < 0.00001), general health (WMD, 7.03; 95% CI, 0.65 to 13.42, P = 0.03), and vitality (WMD, 9.1; 95% CI, 2.50 to 15.69, P = 0.007). Conclusions: The meta-analysis suggested that exercise training improved vascular function in patients with CKD. The exercise program should be considered as one of the management strategies for cardiovascular disease in patients with CKD.